Balance Scorecard Based Performance Analysis At CV Tirta Setra Qusae - Hurriyaturrohman, Hurriyaturrohman; Mandasari, Karina Tranti; Ama, Naoval; Raharjo, Regina Manzilah; Astriyani, Siti Nur; Julyana Sari, Winda (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2024)
The study analyzed the performance of tirta setra qusae's CV's performance using the balanced scorecard approach (BSC) to measure the effectiveness and efficiency of business management. The BSC was selected for being able to integrate performance readings from four main perspectives: finance, customers, internal business processes, and learning and growth. Data collected through documentation financial statements, customer satisfaction surveys, and corporate operations evaluations. Analysis shows that companies have stable financial performance, with a 4.28% return on assets (roa) and return on investment (ROI) at 54,83%. Customer perspectives show a good level of satisfaction, while the perspective of the internal business process and learning and growth reflect increased efficiency and the development of human resource capacity. The study provides a strategic recommendation for improving operational performance and supporting future corporate sustainability.